Improving the Efficiency of Insurance Claim Process with Agile-Based Claim Management System in Cargo Companies - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research identified efficiency issues in the insurance claims process at a freight forwarding company, including the lack of system responsiveness, the complexity of claims handling, and the need for a more adaptive and transparent system. The applied research method focused on developing an Agile-based claims management system, including requirements definition, project planning, system development based on requirements specifications, phased implementation, functional, performance, security, and end-user testing, and analysis of test results. The results showed that implementing the Agile-based system successfully improved the efficiency of the claims process, optimized claims handling, reduced response time, and improved user satisfaction. This research contributes to developing a system that can be applied across industries, improving operational efficiency, customer service, and competitiveness in a competitive market.